1969
DOI: 10.1002/jlac.19697250112
|View full text |Cite
|
Sign up to set email alerts
|

Isolierung von Dibenzyläther‐hydroperoxid aus den Peroxygenaten von Benzylalkohol und Dibenzyläther

Abstract: Durch Peroxygenierung von Dibenzylather (1) und Benzylalkohol (2) entsteht Dibenzylatherhydroperoxid (4). das saulenchromatographisch in 95-bzw. 92.5proz. Reinheit isoliert wird. Saure Hydrolyse von 4 ergibt Benzaldehyd (5). 2 und Wasserxtoffperoxid; katalytische Hydrierung fuhrt zu 5, 2 und Wasser; mit 5 n NaOH entstehen Benzoesaure (6) und 2. Bei der katalytischen Zersetzung von 4 mit Eisen(1I)-sulfat bildet sich Benzoesaurebenzylester (7).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In some other studies of the reactions of β-diketones with hydrogen peroxide, the formation of tetraoxanes was not documented . In the study, presumably bis-tetraoxane was synthesized in high yield from tetraketone (1,1,3,3-tetraacetylpropane) by the sulfuric acid catalyzed reaction with hydrogen peroxide in water at elevated temperature (80 °C). This result is apparently attributed to the specific reactivity of this tetraketone, its good solubility in water, and the relatively high thermal stability of the resulting peroxide.…”
Section: Introductionmentioning
confidence: 98%
“…In some other studies of the reactions of β-diketones with hydrogen peroxide, the formation of tetraoxanes was not documented . In the study, presumably bis-tetraoxane was synthesized in high yield from tetraketone (1,1,3,3-tetraacetylpropane) by the sulfuric acid catalyzed reaction with hydrogen peroxide in water at elevated temperature (80 °C). This result is apparently attributed to the specific reactivity of this tetraketone, its good solubility in water, and the relatively high thermal stability of the resulting peroxide.…”
Section: Introductionmentioning
confidence: 98%
“…Currently, the reaction of ketones or aldehydes with H 2 O 2 and hydroperoxides serves as one of the main synthetic approaches to organic peroxides. Although many publications describe reactions of hydrogen peroxide and monoketones, the problem of peroxidation selectivity in the presence of several reactive centers has not found a general solution. For β-dicarbonyl compounds, this issue has been successfully addressed only in a small number of literature reports. It was shown that β-diketones can be transformed into 1,2,4,5-tetraoxanes, , whereas δ-diketones can be converted into 1,2,4-trioxolanes (ozonides) (Scheme ). , Peroxidation of malonic acids and their esters yields malonyl peroxides (Scheme ).…”
Section: Introductionmentioning
confidence: 99%